أهمية تكنولوجيا المعلومات في دعم التطوير التنظيمي - Zenib Mohamed M. Alfegeh (Abjadia, 2017)
يشير مصطلح تكنولوجيا المعلومات إلى مجموعة المعرفة العلمية والتكنولوجية والهندسية والأساليب والفنون اللازمة لتحويل المدخلات إلى المخرجات، ومن هنا ازداد اهتمام المنظمات بتكنولوجيا المعلومات، وذلك نظراً لدورها الناجح والكبير في الجوانب الإدارية المختلفة، حيث أسهمت في إحداث تغييرات كبيرة وهامة، تمثلت في تخفيض تكاليف العمليات الإنتاجية وتحسين مستويات الأسعار، وزيادة السرعة في الانجاز وتحسين الجودة مما أسهم في زيادة القدرة التنافسية لهذه المنظمات. ويهدف هذا البحث للتعريف بتكنولوجيا المعلومات وأهميتها في دعم التطوير التنظيمي، ومعرفة مراحل تكنولوجيا المعلومات وأهم الخصائص التي تتميز بها، وكذلك معرفة علاقة تكنولوجيا المعلومات والأداء المنظمي، ومعرفة أهم أدوار نظم المعلومات على مستوى المنظمة، ومعرفة أن نظم المعلومات هي سر نجاح كل منظمة. ونستنتج أن امتلاك تكنولوجيا المعلومات واستثمارها أصبح من المعايير الهامة التي يقاس على أساسها تطوُّر البلدان وزيادة قُدرتها التنافسية كما تلعب تكنولوجيا المعلومات دوراً أساسياً في بناء وتطوير وتحسين أداء نظم المعلومات في المؤسسة ولها الآن الدور الأساسي في إعادة تشكيل المؤسسات، بحيث تفرض هذه التكنولوجيا أهمية تطوير نموذجاً إدارياّ يتميز بالانفتاح والمرونة والقُدرة على التكيُّف مع التطوُّرات التقنية.Information technology refers to the range of scientific, technological and engineering knowledge, methods and arts which are needed to transform inputs into outputs. Hence, the organizations' interest toward information technology has increased due to their success and significant role in the various administrative aspects; contributing to significant changes, improving price levels, increasing speed of delivery and improving quality. It contributes in increasing competitiveness of these organizations. The aim of this research is to introduce information technology and its importance in supporting organization development, information technology stages knowledge and its main characteristics, as well as knowledge of the relationship of information technology and organization performance, knowledge of the important roles of information systems at the level of the organization. It is concluded that the acquisition and investment of information technology has become an important criterion on which the development of countries and their competitiveness are measured. Information technology plays an essential role in building, developing and improving the performance of information systems in the enterprise and now it has become the key role in restructuring institutions. Administratively, it is characterized by openness, flexibility and adaptability to technical developments.